Pepón Osorio - my beating heart = Pepón Osorio - mi corazón latiente - Norton, Margot ca. 20./21. Jh; Norton, Margot ca. 20./21. Jh; Mosqueira, Bernardo; Mosqueira, Bernardo (New Museum, 2023)
Informed by his background in theater and performance as well as his experiences as a child services case worker and professor, the richly textured sculptures and installations of Puerto Rican-born, Philadelphia-based artist Pepón Osorio (born 1955) are deeply invested in political, social and cultural issues affecting Latinx and working-class communities in the United States. Published for the artist's most comprehensive exhibition to date, this catalog focuses on the elaborate, large-scale multimedia environments that Osorio has been creating since the early 1990s. Often developed through long-term conversations and collaborations with individuals in the neighborhoods where they were first shown, his installations draw from personal stories in order to empathetically elucidate larger social ills. Taken from an eponymous work, the book's title addresses themes that resonate throughout Osorio's practice, such as the need to better care for one another. (Quelle: artbook.com)